Digital advertising storytelling: consumer educommunication - Elías Zambrano, Rodrigo (IROCAMM - International Review Of Communication And Marketing Mix, 2018)
This is a revision of the concept of digital storytelling to get a definition from a point of view of consumer educommunication. This is how new digital advertising storytelling can modify consumer roles and behaviors. So, in this text, we do a literature revision to explain the advantages of storytelling for digital marketing, the main common mistakes in digital advertising storytelling and what should a good storytelling strategy include. Besides, we make a description about media you have to use, the demand and growth of visual content and other digital marketing Trends for next years.